Oral Problems and Psychological Status of Older Adults Referred to Hospital and Its Relationship With Cognition Status, Stress, Anxiety, and Depression - Shahab Papi; Seyed Vahid Hosseini; Farzaneh Bahadori; Vahideh Rezapour; Amir Mohamad Moghadasi; Reza FadayeVatan (علوم بهداشتی ایران, 2022)
Background and Purpose: Oral health is a critical factor in the quality of life (QoL) of older adults in relation to their nutrition, mental health, and healthy social relationships. This study aimed to investigate oral problems and psychological status of older adults referred to a hospital and its relationship with cognition status, stress, anxiety, and depression. Materials and Methods: This cross-sectional study was conducted among 300 older adults referred to Shahid Beheshti Hospital in Shiraz City, Iran. The “Depression, Anxiety, Stress Scale”, the “Abbreviated Mental Test score”, and the “General Oral Health Assessment Index” were used to collect the required data. The Pearson correlation and multiple linear regression statistical tests were used to analyze the data in SPSS v. 26. P less than 0.05 were considered significant. Results: The Mean±SD age of the participants was 70.1±4.6 years. Their mean±SD score of oral health was 44.83±3.91, and the mean±SD cognitive status was 9.28±0.9. The results of correlation analysis revealed a significant relationship between the dimensions of mental health (cognitive status, stress, anxiety, depression) and oral health (P<0.05). According to the multiple linear regression model, there was a significant relationship between oral health and cognitive status (P=0.002) and between oral health and stress (P=0.015). Conclusion: The study’s results showed a correlation between mental health and oral health. Thus, one of the ways to improve the mental health of the elderly is to provide appropriate and timely dental intervention.